ANALISIS KESALAHAN PENYEBUTAN NOMINAL UANG DALAM BAHASA MANDARIN - Imelda (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
Students will never escape mistakes in learning a language, be it their mother tongue as a first language or a foreign language as a second language. If analyzed, errors in language will help the language learning process be more mature and reasonable. In the process of learning Mandarin, money is something that will be encountered in everyday life. It is common for Chinese learners to make mistakes in mentioning money nominal, considering that there are several different factors in the writing rules and the rules for mentioning money nominal in Rupiah from Indonesia and the Renminbi currency from China. Based on this, the researcher believes that research is needed to analyze the mistakes that Indonesians often make in mentioning money nominal in Chinese so that the results can be observed by both teachers and students of Mandarin so that mistakes do not occur again in practice. Keywords: Mandarin, Nominal Money, Mention